Comparison of test performance on paper-based testing (PBT) and computer-based testing (CBT) by English-majored undergraduate students in China - Wenjing Yu (SpringerOpen, 2021)
Abstract Computer-based testing (CBT), which refers to delivering assessments with computers, has been widely used in large English proficiency tests worldwide. Despite an increasing CBT in China, limited research is available concerning whether CBT can be used for the Test for English Majors-Band 4 (TEM 4). The current study investigated whether testing mode impacted TEM 4 score and factors (i.e., computer familiarity level and attitude towards CBT) that might correlate with performance on CBT of TEM 4. Overall 92 Chinese undergraduate students were randomly assigned to one of the groups, i.e., CBT or paper-based testing (PBT), and took the test. A mixed method was employed, including (1) quantitative and qualitative analysis of test performance in two modes, as well as CBT group participants’ computer familiarity and attitudes towards the mode; and (2) thematic analysis of semi-structured interviews. The results revealed that (1) test scores in CBT and PBT were comparable; (2) two items in the computer familiarity questionnaire, i.e., comfort level of reading articles on the computer and forgetting time when using computers, positively correlated with CBT scores; and (3) participants’ attitude towards CBT did not impact test performance.